First measurement of the β-decay half-life of 206Au. (10th September 2015) - Morales, A. I.; Benzoni, G.; Al-Dahan, N.; Vergani, S.; Podolyák, Zs.; Regan, P. H.; Swan, T. P. D.; Valiente-Dobón, J. J.; Bracco, A.; Boutachkov, P.; Crespi, F. C. L.; Gerl, J.; et al.
Abstract: The β decay of the N = 127 isotone 206 Au has been investigated at the Gesellschaft für Schwerionenforschung laboratory within the rare isotope investigations at GSI Collaboration. From the experimental data, both its half-life and the level structure of the N = 126 daughter nucleus 206 Hg have been extracted. On the basis of the new results, the systematics of Au β -decay half-lives beyond the N = 126 shell closure is discussed. In addition, the interplay between allowed Gamow-Teller and first-forbidden transitions in the N > 126, Z < 82 mass region is reviewed.